Molecular evolution, diversity, and adaptation of foot-and-mouth disease virus serotype O in Asia - Li, Fangtao; Li, Yan; Ma, Jianrong; Wu, Ruizhi; Zou, Xingqi; Liu, Yebing; Zhao, Qizu; Zhu, Yuanyuan (Frontiers in Microbiology, 2023)
Foot-and-mouth disease (FMD) is highly contagious and affects the economy of many countries worldwide. Serotype O is the most prevalent and is present in many regions of Asia. Lineages O/SEA/Mya-98, O/Middle East-South Asia (ME-SA)/PanAsia, O/Cathay and O/ME-SA/Ind-2001 have been circulating in Asian countries. Low antigenic matching between O/Cathay strains and current vaccine strains makes the disease difficult to control, therefore, analyzing the molecular evolution, diversity, and host tropisms of FMDV Serotype O in Asia may be helpful. Our results indicate that Cathay, ME-SA, and SEA are the predominant topotypes of FMDV serotype O circulating in Asia in recent years. Cathay topotype FMDV evolves at a higher rate compared with ME-SA and SEA topotypes. From 2011 onwards, the genetic diversity of the Cathay topotype has increased substantially, while large reductions were found in the genetic diversity of both ME-SA and SEA topotypes, suggesting a trend that infections sustained by the Cathay topotype were becoming a more severe epidemic in recent years. Analyzing the distributions of host species through time in the dataset, we found that the O/Cathay topotype was characterized by a highly swine-adapted tropism in contrast with a distinct host preference for O/ME-SA. The O/SEA topotype strains identified in Asia were isolated mainly from cattle until 2010. It is worth noting that there may be a fine-tuned tropism of the SEA topotype viruses for host species. To further explore the potential molecular mechanism of host tropism divergence, we analyzed the distribution of structure variations on the whole genome. Our findings suggest that deletions in the PK region may reflect a common pattern of altering the host range of serotype O FMDVs. In addition, the divergence of host tropism may be due to accumulated structural variations across the viral genome, rather than a single indel mutation.